Pandangan HAMKA Terhadap Komunisme - Roma Wijaya Roma (Institut Agama Islam Muhammadiyah Sinjai, 2021)
Communism is the notion of common ownership promoted by Karl Marx. The development of communist understanding extends to the political system which appears to be a dictator of the people themselves. In the decision of TAP MPRS No. XXV / MPRS / 1966 prohibits communist organizations in Indonesia. Hamka, a mufassir, a polite and firm scholar in the Al-Azhar commentary, criticizes communist teachings. The main teachings of Communism are a philosophy based on historical materialism, being skeptical of religion and denying the existence of God, eliminating family ties and making women belong together, abolishing individual property rights over the means of production and wealth, struggling roughly and carrying out their ideals with dictatorial-proletarian system. Hamka's interpretation of several verses on which the communist ban was based was Q.S. Al-Jatsiyah (45): 22, Q.S. Yunus (10): 99, Q.S. Al-Anfal (8): 75, and Q.S. Ali Imran (3): 159. Although Hamka does not explicitly comment directly on communism, the implicit meaning of Hamka's interpretation of these verses shows his emphatic criticism.